(untitled) (European Journal of Economics, Finance and Business Development, 2025)
This study presents a comparative analysis of somatic phraseological units (SPUs) in English and Uzbek, with a focus on the scope and depth of research conducted in both languages. Somatic idioms, involving body parts like "heart," "hand," or "eye," reveal deep cultural and cognitive patterns. While English phraseology has been widely studied within various linguistic frameworks, the exploration of SPUs in Uzbek has only recently gained scholarly traction. This paper analyzes key academic contributions, highlights thematic trends, and proposes directions for further research in contrastive linguistics and cultural studies. The article presents theoretical ideas in this regard and proves them with examples.